2007
DOI: 10.1007/s00383-007-2056-x
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the thoracic inlet in children

Abstract: Though various approaches to the thoracic inlet have been described in adults, currently no guidelines exist in children. Reports in the literature of resection of thoracic inlet tumours in children are only anecdotal. Literature was reviewed to assess the various described approaches with reference to suitability in children. Experience with a 3.5-year-old boy having a thoracic inlet ganglioneuroma, using the anterior cervico-thoracic trap door incision demonstrated excellent access and minimal morbidity. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…On the opposite, the trap door is preferred for tumors located in the upper part of the thorax [13][14][15][16]. Due to the close relation with the brachial plexus, Horner syndrome has often been considered an expected consequence in the cervicothoracic tumors, not related to the technique and not preventable [12,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the opposite, the trap door is preferred for tumors located in the upper part of the thorax [13][14][15][16]. Due to the close relation with the brachial plexus, Horner syndrome has often been considered an expected consequence in the cervicothoracic tumors, not related to the technique and not preventable [12,17].…”
Section: Resultsmentioning
confidence: 99%
“…Children 2021, 8, x FOR PEER REVIEW 3 of 13 16]. Due to the close relation with the brachial plexus, Horner syndrome has often been considered an expected consequence in the cervicothoracic tumors, not related to the technique and not preventable [12,17]. A recent new approach has been proposed for the resection of cervicothoracic neuroblastomas, named Cervico-Parasternal Thoracotomy.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Pimpalwar achieved a 99% gross total resection in a localized cervicothoracic neuroblastoma using a transmanubrial technique. This approach, however, requires resection of the first costal cartilage and mediastinal exposure is limited to the anatomy visible at the thoracic inlet, above the subclavian vein [11]. Parikh et al reported the resection of cervicothoracic neuroblastoma in three patients using Dartevelle's approach, requiring resection of the medial clavicular head.…”
Section: Discussionmentioning
confidence: 99%
“…Parikh et al reported the resection of cervicothoracic neuroblastoma in three patients using Dartevelle's approach, requiring resection of the medial clavicular head. In adult series, this has been associated with shoulder girdle instability, delayed post-operative recovery, and bony malunion in up to 42% of patients [11-13]. …”
Section: Discussionmentioning
confidence: 99%
“…Cervicothoracic tumors surrounding cervical vessels and extending from the neck to the upper chest are rare in children and difficult to remove completely because of the complex anatomy of this region. Several surgical approaches have mainly been proposed in the literature on adult procedures, including cervicotomy, anterior thoracotomy, or a combination of both, but without any strong arguments in favor of a specific technique . However, these approaches are not optimal in properly exposing the region and involve a major risk of damage to the neurovascular structures.…”
Section: Introductionmentioning
confidence: 99%